Digital Transformation of Islamic Economy: Potential and Challenges of Fintech and Blockchain in Islamic Financial System - Biyati Ahwarumi (Jurnal Multidisiplin Indonesia, 2024)
This study aims to analyze the strategic role of fintech and blockchain in Islamic finance, focusing on the effectiveness of Islamic financing, smart contract implementation, and asset tokenization such as digital sukuk and zakat. The method used is descriptive qualitative research with a literature study approach and content analysis of secondary data from academic articles, official reports, and case studies of Islamic fintech platforms. The results of the study indicate that Islamic fintech has succeeded in bringing financial services closer to the unbanked and underbanked, while blockchain technology provides transparency and transaction efficiency in accordance with the values ​​of maqashid sharia. However, there are still structural challenges such as unpreparedness of regulations and minimal collaboration between stakeholders. This study contributes to the development of a technology-based Islamic economy and recommends the establishment of a Shariah Digital Sandbox and the development of an interdisciplinary curriculum as a strategic step forward.